2023
DOI: 10.21203/rs.3.rs-3306599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Cyberbullying Detection Through Adaptive External Dictionary in Machine Learning

Hamzeh Qudah,
Mwaffaq Abu Alhija,
Hassan Tarawneh

Abstract: Cyberbullying has escalated due to social media's rapid growth, endangering internet security. Correct these harmful habits. ML is used to research cyberbullying on Twitter. This model is enhanced with adaptive external dictionary (AED). Terms that are negative and positive are produced manually. The dynamic lists of positive and negative words produced by AED sentiment analysis. The dataset has positive and negative tweet columns. Social media's fast expansion has increased cyberbullying, threatening online s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The results show that for the proposed SOSNet, using SBERT, an accuracy score of 92.70% was achieved. In a separate study, Al Qudah et al [22] suggested an improved system for cyberbullying detection utilizing an adaptive external dictionary (AED). The authors employed ML models such as RF, XGB, and CatBoost, and introduced ensemble voting models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that for the proposed SOSNet, using SBERT, an accuracy score of 92.70% was achieved. In a separate study, Al Qudah et al [22] suggested an improved system for cyberbullying detection utilizing an adaptive external dictionary (AED). The authors employed ML models such as RF, XGB, and CatBoost, and introduced ensemble voting models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies, such as [23], [25], [26], employed ML models for a similar purpose. Ensemble models were also explored in [20], [22], making a significant contribution to the efficient detection of cyberbullying. The comparative outcomes given in Table 6 demonstrate that the proposed approach yields superior results when compared to these existing approaches.…”
Section: E Performance Comparison With Existing Studiesmentioning
confidence: 99%